2015
DOI: 10.1371/journal.pone.0133891
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus Gastroenteritis in a Neonatal Unit of a Greek Tertiary Hospital: Clinical Characteristics and Genotypes

Abstract: IntroductionRotavirus (RV) infection in neonatal age can be mild or even asymptomatic. Several studies have reported that RV is responsible for 31%-87% of pediatric nosocomial diarrhea and causes gastroenteritis outbreaks in pediatric and neonatal units.ObjectivesStudy clinical characteristics, genotypes and risk factors of RV infection in neonatal age.MethodsA prospective study was conducted from April 2009 till April 2013 in the neonatal special care unit of the largest tertiary pediatric hospital of Greece.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 54 publications
4
22
0
1
Order By: Relevance
“…The correlations between clinical signs and etiological factors in this study were consistent with other results (17,20,26,27). Fever, diarrhea and stools with blood, mucus and/or pus occurred more frequent in patients with bacterial AGE, while vomiting appeared more often in children with viral infections.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The correlations between clinical signs and etiological factors in this study were consistent with other results (17,20,26,27). Fever, diarrhea and stools with blood, mucus and/or pus occurred more frequent in patients with bacterial AGE, while vomiting appeared more often in children with viral infections.…”
Section: Discussionsupporting
confidence: 91%
“…Występowanie objawów chorobowych w zależności od czynnika etiologicznego, pokazanych w prezentowanej pracy, pokrywa się z doniesieniami innych autorów (17,20,26,27). Gorączka, biegunka oraz patologiczne domieszki w kale częściej obserwowano w infekcjach bakteryjnych, natomiast w AGE o etiologii wirusowej znamiennie częściej występowały wymioty.…”
Section: Discussionunclassified
“…Rotavirus infection in children clinically manifests with several symptoms, such as fever, vomiting and watery, bloodless diarrhoea (25,26). These clinical manifestations are more severe than those of other causes of viral gastroenteritis (27).…”
Section: Discussionmentioning
confidence: 99%
“…Severe complications of rotavirus infection, such as bloody diarrhoea associated with necrotising enterocolitis (NEC) and bowel perforation, have been described (25,26,29). Even though they have not yet been fully elucidated, several factors were associated with the pathogenesis of the disease (30).…”
Section: Discussionmentioning
confidence: 99%
“…Studying stool samples had revealed that Esch.coli were isolated from all 6 studied stool samples in infants with gastroenteritis. Esch.coli gastroenteritis in infants is rare where rotavirus (RV) is responsible for up to 87% of infantile diarrhea (34). Esch.coli is a normal inhabitants of the colon, and therefore, determination of the clinical significance of this isolation depends on the determination of whether the isolated strains were pathogenic or not.…”
Section: Discussionmentioning
confidence: 99%